Sistem Pendukung Keputusan Penerimaan Calon Karyawan Menggunakan Metode Simple Additive Weighting - Simanullang, Siska Kristiana; Simorangkir, Andreas Gerhard (TIN: Terapan Informatika Nusantara, 2021)
Companies really need a professional and enthusiastic workforce to help in the progress of the company. Prospective employees must be able to reach the location of the company, both prospective employees who are in villages or cities. Prospective employees who can be selected are employees who can perform the criteria which are weighted to the criteria set by the owner / leader of the company. Therefore, the Company is making efforts to improve the quality of recruitment of prospective employees. To facilitate the recruitment of prospective employees, the HRD has implemented a conventional system, namely using Microsoft Excel. However, at the recruitment of prospective employees, there are weaknesses faced, namely the HRD has an idea that in assessing prospective employees still using intuition or subjective elements. Because in terms of this assessment it does not consider every criteria and benchmarks for the assessment of prospective employees. So it seems that there is no clear reference or criteria for the assessment standard. For this reason, in order to assist HRD in the recruitment process of prospective employees, a decision support system is needed that can provide information for prospective employees who are accepted or not accepted. So the method used in this decision support system is the Simple Additive Weighting (SAW) Method. The recruitment process for prospective employees with a decision support system using the Simple Additive Weighting (SAW) method is carried out by entering the weight values ​​for each of the criteria and the value of the assessment criteria for each prospective employee. Then the process of calculating the value is carried out, to be able to find out the final results and rank of each prospective employee, either the one with the highest score or the lowest score. So that it can help HRD in making decisions about whether to accept prospective employees or not.